Peningkatan Keterampilan Menyusun Teks Laporan Hasil Observasi Dengan Model Discovery Learning Dan Metode Jelajah Alam Sekitar (JAS) Pada Siswa Kelas VII-10 SMP Negeri 11 Medan - Nurainun Ulfa Dalimunthe; Syamsuyurnita Syamsuyurnita; Rizal Manurung (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research is motivated by the lack of students' ability to compose observation report texts. Based on interviews conducted with previous Indonesian subject teachers, it is known that the cause of the low ability to compose observation report texts is because students find it difficult to express ideas, provide understanding and object details, choose the right diction, spelling and punctuation. Likewise interviews with several students, they stated that the text material of the observation report was quite difficult plus the learning that had been carried out was not interesting. Therefore, to improve the skills of compiling observation report texts, the Discovery learning model and the Exploration of the Surrounding Nature (JAS) method are used. Using Classroom Action Research (CAR), which is often used to improve learning processes and outcomes. The research subjects were class VII-10 students of SMPN 11 Medan. Based on the results of the description and analysis of the discussion of cycle 1 and cycle II data, students' abilities in the Observation Reports (LHO) material increased by 35%. It can be concluded that students' abilities have increased through the discovery model and the JAS method in compiling the text of the Observation Report (LHO).